Effects of female sexual chemosignals on mucosal immunity in BALB/c and C57BL/6 male mice - G. V. Kontsevaya; E. A. Litvinova; M. P. Moshkin (Вавиловский журнал генетики и селекции)
The immune response to immunogenic stimuli depends on various factors like cytokine context, way of entry, and immune status of the organism. In mice, female chemosignal entry into the male organism via the respiratory system causes activation of the mucosal immune response, which leads to the development of enhanced resistance to infections and is of adaptive value. However, the activation of mucosal immunity depends on the genetic predispositions of the immune response. BALB/c and C57BL/6 are prototypically Th2- and Th1-type mouse strains, respectively, therefore, they can serve as perfect model organisms for studying mechanism of lung mucosal immune activation in response to female chemosignals. Respiratory tract mucosal immune response to intranasal application of LPS, urea solution, saline and female urine used as a chemosignal was investigated in BALB/c and C57BL/6 male mice. Application of both female urine and LPS increased total white blood cell count and protein concentration in bronchoalveolar lavage fluid in BALB/c, but not in C57BL/6 male mice, suggesting an important role of Th2 pathway in lung mucosal immune response. At the same time, urine application provoked a significantly lower plasma corticosterone elevation than LPS. Thus, sexual signals associated with infection risks provide genotype-dependent mobilization of innate immunity without significant activation of physiological stress mechanisms.